Influence of distance, geometry and number of control stations on quality of local geodetic networks for the purpose of georeferencing of rural properties - Rosalen, David Luciano [UNESP] (Associação Brasileira de Engenharia Agrícola (SBEA), 2014)
The implementation of local geodetic networks for georeferencing of rural properties has become a requirement after publication of the Georeferencing Technical Standard by INCRA. According to this standard, the maximum distance of baselines to GNSS L1 receivers is of 20 km. Besides the length of the baseline, the geometry and the number of geodetic control stations are other factors to be considered in the implementation of geodetic networks. Thus, this research aimed to examine the influence of baseline lengths higher than the regulated limit of 20 km, the geometry and the number of control stations on quality of local geodetic networks for georeferencing, and also to demonstrate the importance of using specific tests to evaluate the solution of ambiguities and on the quality of the adjustment. The results indicated that the increasing number of control stations has improved the quality of the network, the geometry has not influenced on the quality and the baseline length has influenced on the quality; however, lengths higher than 20 km has not interrupted the implementation, with GPS L1 receiver, of the local geodetic network for the purpose of georeferencing. Also, the use of different statistical tests, both for the evaluation of the resolution of ambiguities and for the adjustment, have enabled greater clearness in analyzing the results, which allow that unsuitable observations may be eliminated.

A implantação de redes geodésicas locais para fins de georreferenciamento de imóveis rurais tornou-se uma obrigatoriedade após a publicação da Norma Técnica de Georreferenciamento pelo INCRA. Conforme essa norma, a distância máxima de linhas-base para receptores GNSSL1 é de 20 km. Além do comprimento da linha-base, a geometria e o número de estações geodésicas de controle são outros fatores a serem considerados na implantação de redes geodésicas. Dessa forma, o objetivo do trabalho foi verificar a influência de comprimentos de linhas-base superiores ao limite normatizado de 20 km, da geometria e do número de estações de controle, na qualidade de redes geodésicas locais para fins de georreferenciamento e, também, demonstrar a importância da utilização de testes específicos na avaliação da solução das ambiguidades e na qualidade do ajustamento. Os resultados indicaram que o aumento do número de estações de controle melhorou a qualidade da rede, que a geometria não influenciou na qualidade e que o comprimento de linha-base sim; mas comprimentos superiores a 20 km não inviabilizaram a implantação, com receptor GPS L1, de rede geodésica local para fins de georreferenciamento. Também, que a utilização de diferentes testes estatísticos, tanto para a avaliação da solução das ambiguidades como para o ajustamento, permitiu maior clareza na análise dos resultados, possibilitando, inclusive, que observações não adequadas possam ser eliminadas.
Influência da distância, geometria e número de estações de controle na qualidade de redes geodésicas locais para fins de georreferenciamento de imóveis rurais
Keywords: GNSS; linha-base; Lei 10.267/2001; GNSS; baseline; Law 10,267/2001